Large-scale radiation and energy balances with Landsat 8 images and agrometeorological data in the Brazilian semiarid region - Castro Teixeira, Antonio Heriberto de; Leivas, Janice Freitas; Tangerino Hernandez, Fernando Braz [UNESP]; Momesso Franco, Renato Alberto [UNESP] (Spie-soc Photo-optical Instrumentation Engineers, 2017)
Aiming to subsidize the rational water resources management, four Landsat 8 (L8) images along different conditions of the year 2014 were used for modeling the radiation and energy balances in the mixed agroecosystems inside a Brazilian reference semiarid area. The SAFER algorithm was applied to calculate the latent heat flux (lambda E); net radiation (R-n) was acquired by the Slob equation; ground heat flux (G) was considered a fraction of R-n; and the sensible heat flux (H) was retrieved by residue in the energy balance equation. For classifying the vegetation, the surface resistance algorithm (SUREAL) was used to estimate the surface resistance to the water fluxes (r(s)) with threshold values for r(s). Clearly, one could see higher lambda E values from irrigated crops (ICs) than those for natural vegetation (NV) with some situations of heat horizontal advection. The respective lambda E, H, and G average ratios to R-n for the ICs ecosystem were 64% to 79%, 18% to 28%, and 3%, respectively. For the NV ecosystem, the corresponding fractions were 4% to 37%, 60% to 94%, and 4%, respectively. The algorithms proved to have strong sensibility to quantifying the large-scale energy and mass exchanges by applying L8 images in mixed agroecosystems of semiarid environments. (C) 2017 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: net radiation; latent heat flux; sensible heat flux; soil heat flux; energy partition